mHealth to Improve the Diet Among Low-Income Populations Enrolled in an Established U.S. Nutrition Program: Design and Rationale of a Randomized Controlled Trial - Heather Noel Fedesco; David A. Evans; David A. Evans; Nolan Kline; William Bart Collins; William Bart Collins; William Bart Collins (Frontiers in Public Health, 2015)
Aim: To describe the theoretical basis, and implementation of a randomized controlled trial to improve the diet and nutrition of low-income families in the United States.